Harvesting time and roasting effects on colour properties, xanthophylls, phytates, tannins and vitamin C contents of orange maize hybrid - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Menkir, A.; Ogunlade, A.O.; Olaofe, O. (Springer, 2020)
Biofortified maize varieties form an essential part of a nutritious diet; available evidence suggests that different processing methods may affect the final food products. The study aimed to evaluate the effects of processing (roasting) and harvesting time on the bioactive components (lutein, zeaxanthin, β-cryptoxanthin, phytate, tannin and vitamin C) and colour properties (L*, a*, b*), of biofortified orange maize. The orange maize hybrids used for the study were obtained from the International Institute of Tropical Agriculture (IITA) diverse lines with high provitamin A (PVA) content. The results showed that harvesting time and roasting methods significantly (P ≤ 0.001) affected the colour properties. The positive values of ∆b* 30.7, 36.0 and 38.1 at 20 days after pollination (DAP), 27DAP and 34DAP, respectively showed that the intensity of orange colour increased with delay in harvesting time. In unprocessed freshly harvested orange hybrid maize; lutein, zeaxanthin, β-cryptoxanthin, tannin and vitamin C increased with an increase in harvesting time. For roasted hybrid, the mean concentrations of all the bioactive components increased with increases in harvesting time except for tannin and vitamin C that showed a decrease at 20DAP and 27DAP. The results revealed that processing and time of harvest affect the levels of non-provitamin A carotenoids, tannins, phytic acid, Vitamin C and the colour properties of biofortified maize genotypes.